2020
DOI: 10.1111/jch.13854
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of self‐reported hypertension: Effect of age, gender, and history of alcohol dependence

Abstract: Patient awareness of medical conditions may influence treatment seeking and monitoring of these conditions. Accurate awareness of hypertension reported to clinicians evaluating patients for whom clinical history is limited, such as in emergency care, can aid in diagnosis by revealing whether measured hypertension is typical or atypical. Measurement of blood pressure in a laboratory study was assessed at rest, immediately before phlebotomy, and within 10 minutes after. The resting measure was used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…These include the fact that we could not directly verify the presence of positive tests for SARS-CoV-2 infection but rather had to rely on the participants self-reports of testing positive and having symptoms and/or health care seeking for the symptoms. However, we believe that this cohort provides accurate responses to questions concerning health behaviors based on previous analyses in which the health behavior in question could be verified by in-person assessment of hypertension ( 23 ). An additional limitation was the form of HLA data available.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These include the fact that we could not directly verify the presence of positive tests for SARS-CoV-2 infection but rather had to rely on the participants self-reports of testing positive and having symptoms and/or health care seeking for the symptoms. However, we believe that this cohort provides accurate responses to questions concerning health behaviors based on previous analyses in which the health behavior in question could be verified by in-person assessment of hypertension ( 23 ). An additional limitation was the form of HLA data available.…”
Section: Discussionmentioning
confidence: 94%
“…A number of studies have reported associations between hypertension and risk for developing COVID-19 ( 11 , 22 ), with more severe consequences being reported in some studies ( 22 ). Based on reliable self report of hypertension in this sample ( 23 ), assessment of hypertension was completed using positive responses to whether or not the participant had been diagnosed with hypertension either currently or in the past. Using the combined report of either, a statistically significant association with reported COVID-19 was not seen.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, our dependent variable is based on a self-reported measure of hypertension, rather than resting seated blood pressure measurements. Prior research has shown that individuals may not be aware that they have hypertension, and while self-reports may underreport the prevalence of high blood pressure, there is general consistency with physician diagnoses [ 73 75 ]. Yet, our prevalence estimates for Black, Latino, and White adults are in line with both self-reported and measured hypertension from nationally representative surveys [ 76 78 ].…”
Section: Discussionmentioning
confidence: 99%
“… 32 In waves 2 and 3, all respondents were asked, ‘In the past 12 months, has a doctor, nurse or other health professional told you that you had high blood pressure?’ Due to a change in the skip pattern in waves 4 and 5, this question was only asked to respondents who reported they saw a ‘medical doctor, nurse, or other health professional’ during the past 12 months. We adopted an inclusive measurement strategy because self-reported hypertension is known to have low sensitivity (ie, it is underestimated) in epidemiological studies, 35 especially among women 36 and non-Hispanic (NH) black adults. 37 To minimise this bias, we classified respondents who answered ‘yes’ to the blood pressure question as having self-reported hypertension regardless of whether they reported seeing a doctor during the past year.…”
Section: Methodsmentioning
confidence: 99%